2011
DOI: 10.1007/s11605-011-1547-1
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of the Short- and Long-Term Results of Randomized Controlled Trials That Compared Laparoscopy-Assisted and Conventional Open Surgery for Rectal Cancer

Abstract: Laparoscopic surgery may be an acceptable alternative treatment option to conventional open surgery for rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 35 publications
6
71
0
10
Order By: Relevance
“…Importantly, analysis of the RCTs included in our study indicated that LPS surgery had similar oncological outcomes to open surgery in terms of OS and disease-free survival [6,8,11,12,14]. Moreover, previous meta-analyses also demonstrated that LPS surgery offered equivalent oncological outcomes to open surgery [18][19][20][21][22][23]. Further studies are needed to validate these results.…”
Section: Discussionsupporting
confidence: 58%
“…Importantly, analysis of the RCTs included in our study indicated that LPS surgery had similar oncological outcomes to open surgery in terms of OS and disease-free survival [6,8,11,12,14]. Moreover, previous meta-analyses also demonstrated that LPS surgery offered equivalent oncological outcomes to open surgery [18][19][20][21][22][23]. Further studies are needed to validate these results.…”
Section: Discussionsupporting
confidence: 58%
“…Consequently, 6 randomized trials presenting data on survival and recurrence were retrieved and showed noninferiority of laparoscopic compared with open resection for rectal cancer in terms of overall and disease-free survival. 20,33,36,37,39,41 The equivalence of these 2 procedures is supported by 3 meta-analyses, [43][44][45] and was confirmed for both anterior and abdominoperineal resections. 20 All trials retrieved included resections of the left, right or sigmoid colon for adult patients with stage I, II or III colon cancer or anterior or abdominoperineal resection of rectal cancer of any stage.…”
Section: Oncologic Outcomesmentioning
confidence: 84%
“…For rectal cancer, 9 phase III randomized clinical trials 11,20,21,[33][34][35][36][37][38][39][40][41][42] and 7 meta-analyses were selected. 28,29,[43][44][45][46][47] No meeting abstracts satisfied the inclusion criteria. The main design characteristics of each randomized trial are summar ized in Table 2 for colon cancer and in Table 3 (Table 1).…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The morbidity (LAC 40%, OC 37%, P = 0.424) and mortality (LAC 1%, OC 2%, P = 0.409) within 28 days of surgery were also similar. The conversion rate was 16%, equivalent to the most recent data 61) . Anastomotic leakage rates were similar between the two groups (LAC 13%, OC 10%, P = 0.462).…”
Section: Long -Term Outcomes (Table 4)mentioning
confidence: 99%